A Comparative Analysis of Universal Basic Education Programme in Nigeria (UBE) and the â€œGrundskolaâ€ Education Programme of Sweden - Opara, Jacinta A (Richtmann Publishing, 2011)
The formation of educational policies is complex by nature. The complexity owes not only to the fact that education is asector where it is difficult to identify the underpinnings and their effects to be foreseen, but also to the diversity of interests thateducation represents for the different actors in society. In the dynamics of educational management, within the large context of aglobal quest for Education for All (EFA), the Nigerian UBE and the Swedish Grundskola programmes have a fundamentalprinciple in common. Compared to other socio-economic sectors, educational development involves more difficult andmultidimensional problems. Faced with financial constraints, governments in many countries are not able to meet the broadsocial demands without adopting restrictive measures within the education sector, while rationalising the use of allocatedresources. Because there are too many actors, variables and the interrelations between these, the result of Education for All(EFA) with the Grundskola was successful perhaps, based on some of the issues discussed while that of the Nigerian UniversalBasic Education (UBE) programme proved abortive.